Framework to automate mechanical-system design using multiple product-models and assembly feature technology. (2017) - Chatziparasidis, Iraklis; Sapidis, Nickolas S.
A standard method-of-work, employed by manufacturers of engineering-to-order (ETO) products, involves primarily a knowledge-based engineering (KBE) system and a 3D mechanical CAD system. The KBE system includes technical guidelines, design rules, facts, 'best practices' and even a company's commercial and business rules. Thus, when a client places a new order, the manufacturer's aim is to employ its KBE system and (hopefully) minimal user involvement to more-or-less automatically produce the complete 3D CAD model and technical drawings of the requested product. The present paper proposes a solution method for this KBE-CAD transformation problem by using two product models, the schematic assembly model (SAM) and the intermediate assembly model (IAM), in this manner: KBE-SAM-IAM-CAD. The SAM is designed to fully employ all sorts of information available in the KBE system, and incorporate that either in the list of 'SAM components' or in the related 'SAM connection rules'. Then, the IAM translates this 'SAM model' into 3D part models and assembly features, in a manner that production of the final 3D mechanical-CAD model is automatic. This paper also describes and demonstrates a complete implementation of the above KBE-SAM-IAM-CAD methodology in a major industry.